Sur les matrices intégrales périodiques pour quelques systèmes d’équations différentielles - Golokvosčius, P. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Голоквосчюс. О периодичности интегральной матрицы некоторых систем дифференциальных уравнений P. Golokvosčius. Kai kurių diferencialinių lygčių sistemų integralinės matricos periodiškumas